A Canada-Ukraine collaborative initiative for introducing inclusive education for children with disabilities in Ukraine: participant perspectives. Issue 1 (2nd January 2016) - Loreman, Tim; McGhie-Richmond, Donna; Kolupayeva, Alla; Taranchenko, Oksana; Mazin, Dymtro; Crocker, Cheryl; Petryshyn, Roman
Abstract : This article examines the experiences of Canadian and Ukrainian educators who collaborated on a 5-year Canadian International Development Agency (CIDA) funded project to develop local capacity to implement inclusive education for children with disabilities in Ukraine. Ukrainian and Canadian educators and project coordinators engage in reflective dialogue aimed at answering questions regarding the successes and challenges faced in the project. The reasons provided for the success of the project and how that success was facilitated were consistent with the literature on what is required for successful inclusive education: positive attitudes, teacher education, appropriate resources, enabling policy and legislation, family support, good pedagogy, leadership, collaboration, and an organized approach. Significant challenges included: language and terminology, negative or resistant attitudes, and the gap between theory and practice. Overall, this project was regarded as successful by study participants, all of whom were able to cite evidence and reasons for this success.